Ten-year results of intense dose-dense chemotherapy show superior survival compared with a conventional schedule in high-risk primary breast cancer: final results of AGO phase III iddEPC trial. (24th October 2017) - Möbus, V; Jackisch, C; Lück, H J; du Bois, A; Thomssen, C; Kuhn, W; Nitz, U; Schneeweiss, A; Huober, J; Harbeck, N; von Minckwitz, G; Runnebaum, I B; et al.
Abstract: Background: Primary breast cancer (BC) patients with extensive axillary lymph-node involvement have a limited prognosis. The Arbeitsgemeinschaft fuer Gynaekologische Onkologie (AGO) trial compared intense dose-dense (idd) adjuvant chemotherapy with conventionally scheduled chemotherapy in high-risk BC patients. Here we report the final, 10-year follow-up analysis. Patients and methods: Enrolment took place between December 1998 and April 2003. A total of 1284 patients with 4 or more involved axillary lymph nodes were randomly assigned to receive 3 courses each of idd sequential epirubicin, paclitaxel and cyclophosphamide (iddEPC) q2w or standard epirubicin/cyclophosphamide followed by paclitaxel (EC → P) q3w. Event-free survival (EFS) was the primary end point. Results: A total of 658 patients were assigned to receive iddEPC and 626 patients were assigned to receive EC → P. The median duration of follow-up was 122 months. EFS was 47% (95% CI 43% to 52%) in the standard group and 56% (95% CI 52% to 60%) in the iddEPC group [hazard ratio (HR) 0.74, 95% CI 0.63–0.87; log-rank P  =   0.00014, one-sided]. This benefit was independent of menopausal, hormone receptor or HER2 status. Ten-year overall survival (OS) was 59% (95% CI 55% to 63%) for patients in the standard group and 69% (95% CI 65% to 73%) for patients in the iddEPC group (HR = 0.72, 95% CI 0.60–0.87; log-rank P  =   0.0007, two-sided). Nine versus two cases of secondary myeloid leukemia/myelodysplastic syndrome were observed in the iddEPC and the EC → P arm, respectively. Conclusion: The previously reported OS benefit of iddEPC in comparison to conventionally dosed EC → P has been further increased and achieved an absolute difference of 10% after 10 years of follow-up.